Childfree Pasca Pernikahan: Keadilan Hak-Hak Reproduksi Perempuan Perspektif Masdar Farid Mas’udi dan Al-Ghazali: bahasa indonesia/inggris - Muhammad Khatibul Umam,; Nano Romadlon Auliya Akbar, (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2021)
(This study highlights the phenomenon of childfree that is starting to happen a lot in marriage. As a relatively new thing in Indonesia, the reproductive rights of a woman (wife) have so far been understood as the prerogative of a man (husband) as classical fiqh also believes it. This study focuses on 2 points, one of which is Masdar Farid Mas'udi's point of view regarding the childfree phenomenon as the antithesis of classical fiqh experts, especially Al-Ghazali.)